Animasi Wayang Sebagai Media Literasi Dan Kreatifitas Anak Berbasis Kearifan Lokal - Sari, Khairunnisa Etika (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
The demands of the digital era 4.0 for pre-school and school-age children reap many challenges that must be faced, including in the world of education. Saturation and low literacy at the child level cannot be avoided because the material presented is inadequate and not packaged in an attractive way so that it is still unable to compete with various content and online games on the internet which are attractive but not educational. Lack of information about expertise, skills and politeness in digital literacy on social media, to avoid hoaxes that are increasingly widespread. The methods we use to find and solve this problem are interviews, observation and literature study. This method uses the help of a qualitative and psychoeducational approach. This new innovation with wayang animation media is expected to be able to answer one form of increasing literacy in children which is carried out both online with digital platforms, and offline, namely face to face by reading stories through performances similar to wayang shows. The results showed that 92% of respondents rated education from the content presented by Aniway which was able to increase children's literacy in learning and creativity.